Drug interactions with antihypertensives (Research, Society and Development, 2022)
Drug interaction (DI) occurs mainly due to self-medication, polypharmacy or prescription errors. Hypertensive individuals usually need more than one drug for treatment, increasing the probability of possible DI proportional to the amount of drugs used, which can lead to different consequences such as changes in the pharmacological effect, adverse reactions, cumulative toxicity, comorbidities or death. The antihypertensive therapeutic class, which is subdivided into several pharmacological classes with the same therapeutic use, is the class that most stands out in DI and antihypertensive drugs from different pharmacological classes can interact with each other and with other classes of medications in general . Thus, the aim of this study was to statistically analyze the main pharmacological classes and the main drugs related to DI with antihypertensive drugs through a systematic literature review selecting works published in the last twenty years. Drug interactions were evaluated according to severity, classified as mild, moderate and severe. The pharmacological classes causing DI with the most frequent antihypertensive drugs were hypoglycemic agents, non-steroidal anti-inflammatory drugs (NSAIDs), diuretics and a combination of two different types of antihypertensive drugs. The antihypertensive drugs that stood out in DI were captopril, enalapril, hydrochlorothiazide, propranolol, atenolol, amlodipine, amiodarone, losartan, spironolactone and furosemide. Therefore, health professionals need to pay attention to adverse reactions arising from these potential MI, notify and intervene when necessary to improve the efficiency of pharmacological treatment, avoiding damage to health.